Mesozoic Collision-Related Structures in the Southern Tarim Basin, W. China: Implications for the Paleo-Tethys Closing Process - Li, Yong; Wen, Lei; Yang, Xian-Zhang; Li, Cheng; Zhang, Liang; Wang, Bin; Chen, Cai; Liu, Ya-Lei; Li, Yue-Jun (Frontiers in Earth Science, 2022)
The Mesozoic syn- and post-collision structures were revealed in the southern Tarim Basin after careful seismic interpretation and field investigation. The syn-collision structures are the Late Triassic thrusts in the piedmonts of W Kunlun and Altun Mountains and the Markit Slope. Not only newly formed thrusts, but also reviving of some pre-existing thrusts, such as the Qarqan fault in the piedoment of the Altun Mountains. The post-collision structures are the Jurassic-Cretaceous normal faults and the horst-graben structures formed with them. The maximum stress (1) direction of the Late Triassic thrusts is SSW-NNE in the piedmont of W Kunlun Mountains and the Markit slope, SSE-NNW in the piedmont of Altun Mountains. They thrust mainly from the Mountains to the Tarim Basin, meanwhile, meanwhile, there are also some Late Triassic back-thrusts in the Markit Slope. They are the syn-collision structures of a collision on the southern margin of the Tarim plate. It is the N Qiangtang - Tarim collision. This Late Triassic collision is an important tectonic event in the complicated closing process of the Paleo-Tethys. The Jurassic-Cretaceous extensional structures are the post-collision structures of this collision.